2018
DOI: 10.3390/toxins10100381
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a Bivalent Non-Purified Recombinant Vaccine against Botulism in Cattle

Abstract: Botulism is a potentially fatal intoxication caused by botulinum neurotoxins (BoNTs) produced mainly by Clostridium botulinum. Vaccination against BoNT serotypes C and D is the main procedure to control cattle botulism. Current vaccines contain formaldehyde-inactivated native BoNTs, which have a time-consuming production process and pose safety risks. The development of non-toxic recombinant vaccines has helped to overcome these limitations. This study aims to evaluate the humoral immune response generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…There was a linear increase in the immune response between the amount of antigen per vaccine dose and the titers of neutralizing antibodies to α and β toxins. This correlation was similar to that found by Otaka et al (2017) when testing concentrations of 100, 200 and 400µg of recombinant Clostridium botulinum neurotoxins C and D in buffalo, and also by Moreira et al (2018) in bovine species.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was a linear increase in the immune response between the amount of antigen per vaccine dose and the titers of neutralizing antibodies to α and β toxins. This correlation was similar to that found by Otaka et al (2017) when testing concentrations of 100, 200 and 400µg of recombinant Clostridium botulinum neurotoxins C and D in buffalo, and also by Moreira et al (2018) in bovine species.…”
Section: Discussionsupporting
confidence: 85%
“…On day 56 after the first vaccine dose, moment in which the vaccine efficiency is evaluated, through the potency test in the target species according to the literature (Moreira et al 2016, 2018, Otaka et al 2017, blood samples were collected by jugular venipuncture. After clot formation, centrifugation was performed at 3000g for 5 minutes to obtain serum, which was stored at -20°C until further use.…”
Section: Methodsmentioning
confidence: 99%
“…The morbidity rate of this disease can range from 0.1 to 100%, and the number of animals affected may depend on the vaccination program performed by the producer [10]. However, the lethality rate is always very high, close to 100% [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…The emergency measures performed during this outbreak, such as vaccination against botulism, the correct disposal of decomposed organic matter in pastures, adequate mineral supplementation, and provision of good quality water and food were decisive to control the disease at the farm [10]. Vaccination is still considered the most effective prophylactic measure, especially when added to other preventive actions [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, studies involving the production and evaluation of clostridial recombinant vaccines have shown that these immunobiological agents are an important alternative to inducing humoral immune responses in farm animals, achieving higher neutralizing antibody titers when compared to conventional commercial vaccines [ 13 , 14 , 15 , 16 , 17 ]. Thus, the objective of this study was to serve as a pioneer in the use, evaluation and comparison of the humoral immune response duration in horses immunized with recombinant vaccines containing different concentrations (100, 200 and 400 µg) of C. perfringens recombinant alpha (rCPA) and beta (rCPB) proteins for 12 months.…”
Section: Introductionmentioning
confidence: 99%